Answer :

We have,

To find: (AB)-1

We know that,

(AB)-1 = B-1A-1

and here, B-1 is given but we have to find A-1 and

Firstly, we find |A|

Expanding |A| along C1, we get

= 1(8 – 6) – 0 + 3(-3 – 4)

= 1(2) + 3(-7)

= 2 – 21

= -19

Now, we have to find adj A and for that we have to find co-factors:

Now, we have



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers